Nitrogen-doped graphene with a three-dimensional architecture assisted by carbon nitride tetrapods as an efficient metal-free electrocatalyst for hydrogen evolution - Gangadharan, Pranav K.; Unni, SreeKuttan M.; Kumar, Nandha; Ghosh, Prasenjit; Kurungot, Sreekumar (Chemelectrochem, 2017)
Current polymer membrane-based electrolyzers use Pt as a cathode catalyst for efficient reduction of water. The high cost of Pt-based catalysts forces researchers to develop alternative electrocatalysts. Here, a simple strategy has been proposed to synthesize a metal-free electrocatalyst for the hydrogen evolution reaction (HER) by high-temperature annealing of graphene oxide-coated melamine foam. The prepared catalyst possesses both structural and functional advantages with its three-dimensional (3D) interconnected arms of carbon nitride (CNx) backbone wrapped with nitrogen-doped graphene (N-RGO) sheets (CNx@N-RGO). CNx@N-RGO faces only a 193 mV overpotential to achieve a current density of 10mAcm(-2), which is far superior to the previously reported Pt-free systems. Along with the high exchange current density 34.7 x 10(-6)A cm(-2) and low Tafel slope of 54 mV dec(-1), CNx@N-RGO follows a Volmer-Heyrovsky mechanism for the HER. DFT calculations show that the synergy between CNx and N-RGO facilitates good electrical coupling between the two moieties and provides optimal binding to H+ ions on the catalyst that, in turn, results in efficient reduction of hydrogen ions.
Keywords: carbon nitride; Density functional theory; electrocatalyst; hydrogen evolution reaction; nitrogen doped graphene

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst